Levels of involvement and understanding in agriculture: the case of Bintulu, Sarawak, Malaysia - Abd Hamid @ Ghazali, Izzah; Wan Yahaya, Wan Asrina (Gupta Publications, 2019)
Agricultural activities are usually considered as sustenance which dominate rural farm areas and solely support household consumption. The purpose of this study is to investigate the types of agricultural activities by Bintulu residents and to understand their comprehension of agriculture. The data presented in this paper focuses on the basic understanding of respondents on agricultural sectors through the distribution of questionnaires at an agricultural event. Our findings indicated that the majority of respondents were male (59.9%), obtained SPM level education (30.7%) and 64.4% participated in agricultural activities in their home. This finding showed that most agricultural activities support their vegetable consumption and to provide income to support household expenses. Their activities are also limited to small acreages of available land for cultivation which focuses on limited soil near their houses with limited profit (<RM1, 000). Hence, these findings may provides significant findings for establishing an approach to help these farmers.